Documentación de la Norma Técnica de Calidad NTC 6.001 en la Constructora Geo Casamaestra S.A.S (2015)
The Geo Casamaestra SAS building company from Armenia in order to improve their processes and become more efficient and consistent they decide to start with the documentation of the Colombian NTC 6001 technical standard with the certainty that in this way can answer your customers with high quality standards and ensuring continuous improvement in all processes from the selection of human talent to delivery of the final product, a transparent and consistently with what is expected and ensuring total satisfaction.Geo Casamaestra SAS works hard and dedicatedly in the documentation of a quality management system for small and medium enterprises with the goal that in the very near future to make the implementation and subsequent certification of the Colombian technical standard NTC 6.001. Based on the above, the internship project aims at developing the instrumentation process quality management system, meeting all requirements and provisions of the Technical Regulations, starting with the development of a current diagnosis of the company and ending with complete documentation of each of the processes with their proper formats and procedures so that continuous improvement in the organization becomes evident.